Influence of Formal Education on Cognitive Reserve in Patients with Multiple Sclerosis - Luerding, Ralf; Gebel, Sophie; Gebel, Eva-Maria; Schwab-Malek, Susanne; Weissert, Robert (Frontiers in Neurology, 2016)
The concept of cognitive reserve (CR) and its influence on cognitive impairment (CI) has attracted increasing interest. 128 patients with multiple sclerosis (MS) from Southern Germany were evaluated during the years 2000 to 2012. 27 neuropsychological (NP) tests were applied regarding Basic Cognitive Functions, Attention, Executive Functions, Visual Perception and Construction, Memory and Learning, Problem Solving, and Language. By this retrospective approach, a comprehensive neuropsychological profile of the investigated individuals was established. An effect of timespan of formal education on CR was observed. Enrichment by reading, physical activities, and challenging vocational practices had more profound effects in patients who had undergone a shorter educational period compared to a longer educational period. In summary, our study demonstrates that the advantage of longer formal education periods, compared to shorter formal education periods, can be counterbalanced by high frequencies of reading, physical activities, and challenging vocational practices in patients with MS.